2019
DOI: 10.1186/s13041-019-0435-6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of circuit-specific morphological adaptations in ventral tegmental area dopamine neurons by chronic morphine

Abstract: Chronic opiate exposure induces neuroadaptations in the mesocorticolimbic system including ventral tegmental area (VTA) dopamine (DA) neurons, whose soma size is decreased following opiate exposure. Yet it is now well documented that VTA DA neurons are heterogeneous, with notable differences between VTA DA neurons based on their projection target. Therefore, we sought to determine whether chronic morphine induced similar changes in the morphology of VTA DA neurons that project to the nucleus accumbens (NAc) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…5,6 However, whether chronic morphine treatment leads to structural plasticity in the spinal cord is not fully understood, although much evidence showed that morphine addiction alters the density of dendritic spines in several brain regions, including nucleus accumbens (NAc), medial prefrontal cortex (mPFC), ventral tegmental area (VTA), and hippocampus. [46][47][48][49] In the present study, we observed for the first time that repetitive administration of morphine produced a prominent remodeling of synaptic dendritic spines in superficial spinal dorsal horn neurons, as characterized by increased spine density as well as spine morphological changes. Combined deletion of TRPC1, TRPC4, and TRPC5 proteins dampens both spinal spine remodeling and synaptic LTP induced by chronic morphine treatment, which provides a novel mechanistic basis for morphine-induced hyperalgesia and analgesic tolerance.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…5,6 However, whether chronic morphine treatment leads to structural plasticity in the spinal cord is not fully understood, although much evidence showed that morphine addiction alters the density of dendritic spines in several brain regions, including nucleus accumbens (NAc), medial prefrontal cortex (mPFC), ventral tegmental area (VTA), and hippocampus. [46][47][48][49] In the present study, we observed for the first time that repetitive administration of morphine produced a prominent remodeling of synaptic dendritic spines in superficial spinal dorsal horn neurons, as characterized by increased spine density as well as spine morphological changes. Combined deletion of TRPC1, TRPC4, and TRPC5 proteins dampens both spinal spine remodeling and synaptic LTP induced by chronic morphine treatment, which provides a novel mechanistic basis for morphine-induced hyperalgesia and analgesic tolerance.…”
Section: Discussionsupporting
confidence: 54%
“…Opioid‐induced spinal LTP at nociceptor synapses in the spinal cord is now considered to be an essential contributor to opioid‐induced hyperalgesia, and may also analgesic tolerance 5,6 . However, whether chronic morphine treatment leads to structural plasticity in the spinal cord is not fully understood, although much evidence showed that morphine addiction alters the density of dendritic spines in several brain regions, including nucleus accumbens (NAc), medial prefrontal cortex (mPFC), ventral tegmental area (VTA), and hippocampus 46‐49 . In the present study, we observed for the first time that repetitive administration of morphine produced a prominent remodeling of synaptic dendritic spines in superficial spinal dorsal horn neurons, as characterized by increased spine density as well as spine morphological changes.…”
Section: Discussionmentioning
confidence: 49%
“…An inverted projection pattern was previously reported in rodents and primates ( Fallon and Moore, 1978 ; Gerfen, 1985 ; Haber et al, 2000 ), but it has not been observed consistently across all studies ( Matsuda et al, 2009 ; Prensa and Parent, 2001 ); therefore, it has not been depicted in recent models of SNc projections to the CP ( Björklund and Dunnett, 2007 ; Vogt Weisenhorn et al, 2016 ). Potential overlap of Sox6 + and Sox6 − axonal arbors as shown here and in a recent study ( Simmons et al, 2019 ), together with the diverging criteria used to define the dorsoventral division of the SNc and the partially intermingled nature of these neurons, all may be reasons for these inconsistent findings. Importantly, these anatomical findings can explain the patterns of striatal innervation observed in PD brains ( Kordower et al, 2013 ); fibers projecting to the medial striatum are likely preserved because they originate from relatively spared Sox6 − neurons in the dSNc, most of which are also Calb1 + .…”
Section: Discussionmentioning
confidence: 50%
“…The VTA is one of the major sites of dopamine synthesis. The VTA dopaminergic neurons are implicated in the regulation of emotional and motivational behaviors and are involved in the development of psychopathologies including depression [ 50 ], aggression [ 51 ], and addictions [ 52 , 53 ]. So, it was important to check if the prioritized genes could be implicated in VTA dopaminergic signaling.…”
Section: Discussionmentioning
confidence: 99%